Integration of Metabolome and Transcriptome Studies Reveals Flavonoids, Abscisic Acid, and Nitric Oxide Comodulating the Freezing Tolerance in Liriope spicata - Peng, Zhen; Wang, Ye; Zuo, Wen-Tian; Gao, Yue-Rong; Li, Run-Zhi; Yu, Chun-Xin; Liu, Zi-Yan; Zheng, Yi; Shen, Yuan-Yue; Duan, Liu-Sheng (Frontiers in Plant Science, 2022)
Liriope spicata is an evergreen perennial ornamental groundcover with strong freezing tolerance. However, the molecular mechanism underlying freezing tolerance is still unclear in L. spicata. In this study, a comprehensive investigation of L. spicata freezing tolerance was conducted at the levels of physiology and biochemistry, metabolite, and transcript during the stress treatment. There were 581 unique differentially expressed metabolites (DEMs) and 10444 unique differentially expressed genes (DEGs) between freezing treatment and normal cultured plant in leaves. Integrated analysis of metabolomics and transcriptomics showed that flavonoid biosynthesis, carbohydrate metabolism, amino acid metabolism, lipid metabolism, and signal transduction pathways were prominently enriched in response to freezing stress in L. spicata. Here, we identified genes and metabolites involved in flavonoid pathway, abscisic acid (ABA) biosynthesis, and oxidative synthesis pathway of nitric oxide (NO), which may form a regulatory network and play a synergistic effect in osmotic adjustment, reactive oxygen species (ROS) homeostasis, and stomatal closure under freezing stress. These results provide a comprehensive network of flavonoids, ABA, and NO comodulating freezing tolerance in L. spicata.